Urban Decay or the Uncanny Return of Dionysus: An Analysis of the Ruins in Shelley's 'Ozymandias'. Issue 1 (1st March 2022) - Datli Beigi, Roohollah; Abbasi, Pyeaam; Jannessari Ladani, Zahra
Abstract: Written in the familiar genre of ruin poems, Percy Bysshe Shelley's 'Ozymandias' (1818) is well-expressive of the poet's profound hatred of tyranny. One of the distinctive features of the poem is the vividly visual images it provides of the ruined statue and the desert as the setting of the poem. Focusing on the images of the desert and ruins, and using the concept of urban decay and mytho-archetypal notions, this study attempts to show that the ruins of the poem anticipate the modern phenomenon of urban decay as the return of the repressed in city-forms. However, what the poem presents as destruction, death, ruins and decay is in fact the potential of bringing about spring and regeneration. Reading this poem in the light of the mentioned concepts provides the reader with an understanding of the function of the ruins in Shelley's poems as an uncanny Dionysian defiance against both the tyranny of his age and the rationalism of the Enlightenment period.